EKSISTENSI BANK TANAH DALAM PENGELOLAAN PERTANAHAN INDONESIA UNTUK MEWUJUDKAN REFORMA AGRARIA BERDASARKAN UNDANG-UNDANG NOMOR 11 TAHUN 2020 TENTANG CIPTA KERJA (STUDI PERBANDINGAN DENGAN BANK TANAH NEGARA BELANDA) - Olivia Marloanto (Fakultas Hukum Universitas Tarumanagara, 2022)
The purpose of this study is to analyze land banks in Indonesia's land management to realize agrarian reformbased on Law Number 11 of 2020 concerning Job Creation. The type of research used is normative legalresearch. The results of the study found that the concept of a land bank in Indonesia is a mandate as stated inarticle 33 paragraph 3 of the 1945 Constitution of the Republic of Indonesia and article 2 of the UUPA, thatthe state has an important role in the implementation of the land bank. In addition, there are special rules thatbecame the beginning of the emergence of the land bank concept, namely Law Number 11 of 2020 concerningJob Creation. Furthermore, there are implementers of the provisions of this Job Creation Act, namelyGovernment Regulation Number 64 concerning 2021 concerning the Land Bank Agency. The Land Bank hasa very important role in provding land for various development purposes in Indonesia. The role of the LandBank is strengthened in the form of a special agency that manages land for the realization of a just economy.The function of the Land Bank is to ensure the availability of land in the context of realizing a just economythrough planning, land acquisition, land acquisition, land management, land use and land distribution. LandBank's land assets are state assets which are separated from state assets.